1993
DOI: 10.1177/000331979304400308
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Arteriosclerotic Obstruction by LDL Adsorption

Abstract: According to the authors' clinical analysis, about half of the patients who suffer from arteriosclerotic obstruction (ASO) in the lower extremity(-ies) with clinical manifestation are dyslipidemic (total cholesterol > or = 220 mg/dL or LDL cholesterol > or = 140 mg/dL). As suggested by clinical success in regression of ASO in the coronary arteries as a result of aggressive removal of LDL, LDL adsorption utilizing an extracorporeal circulation technique with a dextran sulfate/cellulose adsorbent column was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 2 publications
0
34
0
1
Order By: Relevance
“…Multiple mechanisms appear to be involved in the rapid response. A drastic reduction in LDL cholesterol reduces blood viscosity [35] and improves erythrocytic deformability [36] . Moreover, the removal of clotting factors, namely factor VIII and von Willebrand factor, helps improve the hemorheological picture [5,6,37] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms appear to be involved in the rapid response. A drastic reduction in LDL cholesterol reduces blood viscosity [35] and improves erythrocytic deformability [36] . Moreover, the removal of clotting factors, namely factor VIII and von Willebrand factor, helps improve the hemorheological picture [5,6,37] .…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with this evidence, there is a finding that blood flow to the lower limbs is enhanced by plasma exchange [5]. Based on these findings, LDLapheresis has been also applied for the treatment of PAOD [6,7]. LDL-apheresis is also known to retard the progression of coronary atherosclerosis as shown by a prospective, open, randomized study (the LDLApheresis Atherosclerotic Regression Study: LAARS) [8].…”
Section: Introductionmentioning
confidence: 97%
“…LDL-apheresis has been shown to change peripheral and cerebral haemodynamics favourably by short term improvements in the rheological properties of whole blood and probably also by restoring endothe lium-dependent vasodilation [74,75]. The application of this method may offer opportunities in the preven tion of progression of atherosclerosis as has been shown in selected patients with a primary hyperlipidaemia and established CAD or PVD refractory to drug treatment [24,37,38,[76][77][78][79][80][81].…”
Section: Ldl-apheresismentioning
confidence: 99%
“…Most of these tiñáis have shown slowing or arrest of progression of coronary atherosclerosis. Reports concerning femoral atherosclerosis are more scarce [7,[14][15][16]21,24,25], In several recent clinical trials on plasma lipid regu lation, measurements of carotid artery intima-media thickness (IMT) have been included, because coro nary and carotid atherosclerosis share coronary events as their major cause of morbidity and mortality [38][39][40][41]. Indeed, most of these studies have also shown a slowing of progression of IMT during lipid-lowering treatment.…”
Section: Introductionmentioning
confidence: 99%